2010
DOI: 10.1111/j.1463-1326.2009.01184.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the inter‐relationship between improved glycaemic control, hypoglycaemia and weight change within a long‐term economic model

Abstract: The results of this analysis quantify the QALY decrement that may result from adverse therapy effects. The beneficial effects of improved glycaemic control on QALYs may be offset by characteristic treatment-specific adverse effects, such as weight gain and hypoglycaemia frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 36 publications
3
31
0
2
Order By: Relevance
“…Subsequently, this model represents a plausible approach to assess the value of improving glycaemic control, hypoglycaemia incidence and body weight in populations not reflective of the DCCT/EDIC study cohort, such as those over 60 years of age, or with a long duration of Type 1 diabetes. Furthermore, the impact of weight, hypoglycaemia and HbA 1c on predicted QALYs in this study are consistent with published analyses using the Cardiff Type 2 Diabetes Model 25; and the structure and performance of both Cardiff models have undergone rigorous scrutiny at several Mount Hood Diabetes Challenge Meetings 33, 34, 35.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Subsequently, this model represents a plausible approach to assess the value of improving glycaemic control, hypoglycaemia incidence and body weight in populations not reflective of the DCCT/EDIC study cohort, such as those over 60 years of age, or with a long duration of Type 1 diabetes. Furthermore, the impact of weight, hypoglycaemia and HbA 1c on predicted QALYs in this study are consistent with published analyses using the Cardiff Type 2 Diabetes Model 25; and the structure and performance of both Cardiff models have undergone rigorous scrutiny at several Mount Hood Diabetes Challenge Meetings 33, 34, 35.…”
Section: Discussionsupporting
confidence: 87%
“…Recent studies have reported the health economic value of improved disease management in Type 2 diabetes 25, and estimated the potential costs avoided that a modest HbA 1c reduction would achieve within the UK healthcare system 7. In the present analysis, we quantified the health economic burden of inadequate Type 1 diabetes management in the UK, and estimated the value associated with incremental HbA 1c improvements, fewer hypoglycaemic events and reduced BMI in people with Type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] Conversely, strict glycemic control may increase the risk of hypoglycemia [3,4] which, in some cases, may even offset the expected beneficial effects of good glycemic control. [5] Therefore, hypoglycemia may be an obstacle for good glycemic control and should be an important factor to consider when determining the optimal glycemic target during the selection of medications. This condition is not only observed in clinical practice and tends to develop more frequently in patients with type 1 diabetes and those being treated with insulin, [6] but also reported in patients taking oral hypoglycemic agents.…”
Section: Introductionmentioning
confidence: 99%
“…A previously published and validated economic model, Cardiff Diabetes Model, was used in this study [49][50][51][52]. It is a patient level fixed-time increment, Monte Carlo micro simulation model designed to evaluate the long-term cost-effectiveness of comparable diabetes treatments (a "treatment" arm versus a "control" arm).…”
Section: Cost-effectiveness Modelmentioning
confidence: 99%